Combining Teaching Strategies, Learning Strategies, and Elements of Super Learning Principles - Pllana, Duli (Advances in Social Sciences Research Journal, 2021)
Blending teaching strategies, learning strategies, and elements of super learning principles increase learning outcomes tremendously in any case, situation, or academic subject. Employing teaching and learning strategies adequately impact on an interactive session (academic subjects or any field) to a great degree, enhance learners’ motivation significantly, improve self confidence and self esteem of learners considerably, and soar learning outcomes substiantly. It is impossible to combine all learning and teaching strategies (there are many techniques, and a small space time to incorporate them in one lesson or an academic subject.) in an academic subject entirely. Accordingly, strategic teaching or learning establishes skills or techniques in addressing a lesson or digesting information from the lesson. Also, learning results depend on the quantity and quality of combining learning and teaching strategies, and components of super learning principles. The greater the participation of mixing techniques or skills in a lesson, the greater are the positive results in the learning outcomes. Teaching and learning strategies, and superlearning elements are in a close relationship with each other; teaching strategies imply learning strategies and elements of super learning. Combination of the three ingredients play a crucial part in any lesson, academic subject, or general knowledge; mixing all these three components together wisely maximizes learning outcomes enormously.